Tantangan Perempuan Jawa Di Era Milenial Dalam Menghadapi Disfungsi Sosialisasi Di Lingkungan Keluarga - Debi Setiawati; Fatmawati (Universitas Insan Budi Utomo, 2023)
Javanese women are known to have a position as sigaraning lives and co-wingking for husbands having complex meanings, which must be able to place themselves as partners who are commensurate with their husbands and able to provide encouragement from behind or become Tut Wuri Handayani. In this study will focus on the challenges faced by Javanese women in the millennial era, especially in carrying out the role of socialization in the family. The demands of economic needs and gender equality in the millennial era caused Javanese women to have freedom in public and domestic spaces. The challenges of Javanese women in the millennial era included having a strong mentality in dealing with various situations, having broad insight, having an independent attitude, having a thinking style creative, have high self-confidence and can build a broad public space. The need for communication and information in the millennial era is characterized by high dependence on the use of gadgets, causing women to lose their role in socialization in families such as educating children, planting character values, playing children, introducing religious and cultural values, assisting in learning, teaching ethics of manners and character. For this reason, the hegemony of technological sophistication can eliminate the role of women's socialization in the family. Besides that, the phenomenon of Javanese women who work or have a career loses their role in socializing with children, they are more entrusted to household assistants, child care services, parents and baby sisters.